2008
DOI: 10.1016/s1015-9584(08)60049-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of Colour Doppler Imaging in Detecting Prostate Cancer

Abstract: Colour Doppler and greyscale sonography should be routinely performed to improve detection of prostate carcinoma and to target the lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…In general, the sensitivity and specificity of combined evaluation have been reported to be between 33-88% and 57-85%. [24][25][26] In our study, sensitivity was calculated as 51%, specificity 83%, PPV 60% and NPV 77% when TRUS and CDU were combined. If CDU was added to the TRUS for the decision to perform a biopsy and the biopsy was not performed when CDU was negative, 4 cancer cases (14%) would not be caught.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the sensitivity and specificity of combined evaluation have been reported to be between 33-88% and 57-85%. [24][25][26] In our study, sensitivity was calculated as 51%, specificity 83%, PPV 60% and NPV 77% when TRUS and CDU were combined. If CDU was added to the TRUS for the decision to perform a biopsy and the biopsy was not performed when CDU was negative, 4 cancer cases (14%) would not be caught.…”
Section: Discussionmentioning
confidence: 99%
“…Both these findings were found to be significantly associated with malignancy. Vascularity and its intensity and pattern are the Doppler characteristics that are generally focused on for malignancy detection, and almost all studies focus on this characteristic [ 17 , 20 - 21 , 23 ]. In the present study, we focused on moderate and focal hypervascularity as the diagnostic criteria for color doppler.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of TRUS and color Doppler has resulted in varying diagnostic efficiency in different studies. Generally, the sensitivity of the combined evaluation has been shown to lie in the range 33% [ 22 ] to 88.23% [ 23 ] and specificity has been shown to lie between 57% [ 23 ] and 85% [ 23 - 24 ]. Drudi et al (2006) [ 24 ], in their study, set their eyes on selecting more-specific criteria and could achieve poor sensitivity (38.5%) but high specificity (85%).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies have suggested that CDUS may improve the radiographic sensitivity of GSUS. [38;39] In his study of 31 men with clinically organ-confined prostate cancer who underwent cryo-hemiablation, Bahn et al utilized CDUS to thoroughly examine the prostate, target suspicious lesions, and lateralize the cancer. At a mean follow up of 70 months, 92% (26/28) achieved biochemical disease-free status using the ASTRO definition, 96% (24/25) of those who underwent repeat biopsy had negative results, and 89% (24/27) had maintained their potency despite some requiring phosphodiesterase-5 inhibitors initiation.…”
Section: Ultrasound Guidance In Focal Therapy Of Prostate Cancermentioning
confidence: 99%